El simbolismo de la comida arequipeña - Cornejo Velásquez, Hernán (2006)
This article explains the imaginary and subjective qualities of the food Arequipa. Also their functional aspects, where the variety of plates is directed to cohesionar, to foment identity, to diminish tensions and to homogenize the social classes; equally, to model the behaviors, behaviors and to activate the operation of the organs of the body, to order the daily life in diets fidex for the week and fixed schedules. Also, I highlight the historical character of the foods, where each plate has a history that registers the times of abundance and shortage. I analyze the structural factors of the foods, the sensitive qualities and the meaning of that sweet-salted, the sour-spicy one, as well as the symbolic oppositions of «house» food and of «street», and the social hierarchies of the foods. Finally, I examine the psychoanalytical dimension that has the food to reveal the erotic imagination, the enamoramiento, to assure the fecundity as well as to affirm the life, to be socialized and, even to make fun of the death.